2021
DOI: 10.1186/s13578-021-00568-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SARS-CoV-2 proteins reveals Orf6 pathogenicity, subcellular localization, host interactions and attenuation by Selinexor

Abstract: Background SARS-CoV-2 causes COVID-19 which has a widely diverse disease profile. The mechanisms underlying its pathogenicity remain unclear. We set out to identify the SARS-CoV-2 pathogenic proteins that through host interactions cause the cellular damages underlying COVID-19 symptomatology. Methods We examined each of the individual SARS-CoV-2 proteins for their cytotoxicity in HEK 293 T cells and their subcellular localization in COS-7 cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 53 publications
(76 reference statements)
13
121
3
Order By: Relevance
“…Other factors bind to the nucleocytoplasmic transport machinery, including NSP4 (which interacts with GP210), NSP9 (which associates with Nup54, Nup58, Nup62, Nup88, and Nup214), NSP15 (which binds to NTF2), and ORF6 (which interacts with the Nup98–RAE1 complex) ( 179 ). Indeed, this last interaction has been confirmed by several other groups ( 180 , 181 , 182 , 183 ) and was shown to disrupt bidirectional nucleocytoplasmic transport, likely inhibiting host response to viral infection ( 183 ). This interaction also blocks nuclear translocation of STAT1 to antagonize IFN signaling ( 181 ).…”
Section: Coronavirusesmentioning
confidence: 67%
See 3 more Smart Citations
“…Other factors bind to the nucleocytoplasmic transport machinery, including NSP4 (which interacts with GP210), NSP9 (which associates with Nup54, Nup58, Nup62, Nup88, and Nup214), NSP15 (which binds to NTF2), and ORF6 (which interacts with the Nup98–RAE1 complex) ( 179 ). Indeed, this last interaction has been confirmed by several other groups ( 180 , 181 , 182 , 183 ) and was shown to disrupt bidirectional nucleocytoplasmic transport, likely inhibiting host response to viral infection ( 183 ). This interaction also blocks nuclear translocation of STAT1 to antagonize IFN signaling ( 181 ).…”
Section: Coronavirusesmentioning
confidence: 67%
“…Verdinexor was demonstrated to inhibit the infection of respiratory syncytial virus, VEEV, IAV, EBV, KSHV, AdV-5, as well as HPV-11 ( 297 , 298 , 299 , 300 ). More recently, studies revealed that selinexor, another nuclear export inhibitor that selectively binds CRM1, could be repurposed to directly target the interaction between the SARS-CoV-2 protein ORF6 and other host proteins such as Nup98-RAE1 ( 179 , 182 ). Although none of the drugs has been approved in clinical trials for treating viral infections, these studies show that the comprehensive understanding of the crosstalk between nucleocytoplasmic transport and host antiviral immune responses to viral infection, together with high-throughput drug screening, will contribute to the development of novel antiviral therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ORF6 gene is common to all Sarbecoviruses , including SARS-CoV and SARS-CoV-2, and no orthologues have been found in other Betacoronaviruses , such as MERS-CoV. The protein encoded by SARS-CoV-2 ORF6 gene is 61 aa residues and has been localized to the endoplasmic reticulum and membrane of vesicles such as autophagosomes and lysosomes ( 34 ). SARS-CoV-2 ORF6 protein, is a potent IFN antagonist, a role that was previously described by Kopecky-Bromberg and coworkers in SARS-CoV ( 35 ).…”
Section: Accessory Proteins Of Sars-cov-2mentioning
confidence: 99%